Using Simulation Evaluation for Prelicensure Nursing Program Review. Issue 1 (January 2021) - Thomas, Christine M.; Yocom, Danielle; Kaulback, Michelle; Meehan, Carolyn D.
Abstract : Background: Faculty in a prelicensure baccalaureate nursing program were interested in establishing a process for use of simulation for the evaluation of program outcomes. Problem: Several infrastructure barriers existed for the implementation of simulation for a fair, valid, and reliable student evaluation. Approach: Faculty chose to evaluate student performance in simulation to examine student achievement of program outcomes. Conclusions: The project informed curricular decisions moving forward, helped faculty to standardize scenarios, and outlined a process of establishing validity and reliability that could be implemented in the future for student evaluation.